Diallel analysis of maize hybrids for agronomic and bromatological forage traits - Mendes, Matheus Henrique Silveira; Pereira, Carlos Henrique; Souza, João Cândido de (Acta Scientiarum. Agronomy, 2015)
The aim of this study was to evaluate a diallel of maize hybrids for traits related to forage production and nutritional value. Six commercial hybrids were used as parents. The crosses were made according to a complete diallel design, obtaining the F1 and reciprocal crosses. The evaluations were performed in the main and second crop seasons in the 2010/2011 crop year at the Center for Technological Development in Agriculture of the Federal University of Lavras, located in Lavras, Minas Gerais State, Brazil. The experimental precision indicated by the coefficient of variation was good for all the traits measured. Significant differences were not observed among the crosses for traits related to the nutritional value of the forage. For fresh matter yield and dehusked ear yield, the general combining ability (GCA) and specific combining ability (SCA) effects were significant. Sowing in the second crop season reduced the yield and nutritional value of the forage. The interaction among the crosses and sowing seasons was not significant. For the beginning of an intrapopulational breeding program, the parent BM 3061 stands out by showing high estimates of GCA for the grain and forage yields.